Re-evaluating Ceramic Economy at Ayala (AD 1–1250), Granada, Pacific Nicaragua - Dennett, Carrie L. (2018)
Located on the flanks of Mombacho volcano to the southeast of Granada City, Ayala was the largest occupied center in the area until roughly AD 800, after which its prominence declined. Investigations in the 1990s determined that the site likely played an important local sociopolitical role, as well as being connected to distant groups along vast networks. This interpretation derived, in part, from ceramic evidence including the earliest compositionally verified polychromes manufactured in Pacific Nicaragua ca. AD 500–800 (e.g., Momta and Belo polychromes) and a variety of ceramic types associated with west-central Honduras and El Salvador (e.g., Usulután negative resist and Las Vegas polychromes). Yet, evidence for the (re)distribution of those wares to other known sites in Pacific Nicaragua was lacking. Recent recovery of Ayala’s polychromes at the 13 km-distant site of El Rayo, however, has drawn the site back to the foreground of study. Coupled with advances in volcanology and geochemistry, compositional analyses (INAA and petrography) not only challenge long-held assumptions about the organization of the ceramic economy in Pacific Nicaragua, but also amplify our understanding of Ayala’s specific role within the revised model. Results indicate that (a) Ayala’s unique polychromes were manufactured, at least in some measure, for off-site mortuary-related destinations, (b) the site was only sporadically receiving vessels from west-central Honduras, more frequently creating well-crafted local versions, and (c) rather than simply a consumer of key diagnostic styles after AD 800 (e.g., Papagayo Polychrome) as previously assumed, Ayala was a principal producer and distributor, if not a leader in their development.